Residual Cholesteatoma After Endoscope-guided Surgery in Children. Issue 2 (February 2016) - James, Adrian L.; Cushing, Sharon; Papsin, Blake C.
Abstract : Objective: Endoscopes can facilitate surgery within tympanomastoid recesses that are not visible with the operating microscope. This study investigates whether use of endoscopes to guide dissection of cholesteatoma leads to lower rates of residual cholesteatoma than using the endoscope only for inspection after microscope-guided dissection. Study Design: Comparative cohort study. Setting: Tertiary pediatric center. Patients: Two hundred thirty-five patients with acquired or congenital cholesteatoma in children <18 years having intact canal wall surgery and follow-up >12 months. Interventions: Comparison of group (A) microscope surgery followed by endoscopic inspection, with group (B) endoscope-guided dissection. Main Outcome Measures: Residual cholesteatoma rates, controlling for site of initial cholesteatoma, detection by second-stage surgery, and length of follow-up. Results: Analysis of all patients showed endoscopic dissection was associated with less residua in the middle ear (risk difference = 0.12; p = 0.026, Kaplan–Meier log rank analysis; number needed to treat = 9) but not at other sites. When restricting analysis to ears that were evaluated with second look surgery, no significant reduction in residual disease was found after endoscopic dissection at any site (e.g., retrotympanic residua: 12% Group A versus 7% Group B (NS, Fisher exact test). Endoscopic dissection allowed more permeatal surgery. No complications were attributable to endoscope use. Wound complications occurred in 4% of open cases. Conclusion: Endoscopes enhance surgical access to tympanomastoid recesses. In conjunction with the availability of the operating microscope, angled instruments, and KTP laser, endoscope-guided dissection provides a small incremental benefit for prevention of residual cholesteatoma, and facilitates a minimally invasive approach.